THE INFLUENCE OF DIGITAL LEADERSHIP AND DIGITAL TRANSFORMATION ON EMPLOYEE WORK EFFECTIVENESS IN GOVERNMENT AGENCIES IN GUNUNGSITOLI CITY - Tolona Gea; Maretta Ginting; Kuras Purba; Santi Rizki; Eva Solita Pasaribu (CV. Radja Publika, 2026)
Digital transformation in the government sector requires organizations to implement adaptive leadership and technology-based work systems to improve employee work effectiveness. This study aims to analyze the influence of Digital Leadership on employee work effectiveness, the influence of Digital Transformation on employee work effectiveness, and the influence of both variables simultaneously on the Regional Government Organization of Gunungsitoli City Government. The study used a quantitative approach with a questionnaire distribution method. The population was 1,468 people with a research sample of 94 employees selected using purposive sampling. Data were collected through a Likert scale questionnaire with a research instrument that had met validity requirements with a Corrected Item-Total Correlation value greater than 0.30 and reliability with a Cronbach's Alpha value of each variable above 0.70 and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results showed that Digital Leadership had no significant effect on employee work effectiveness with a regression coefficient of 0.080 and a significance value of 0.559 (>0.05). In contrast, Digital Transformation has a positive and significant effect with a regression coefficient of 0.489 and a significance value of 0.000 (<0.05). Simultaneously, Digital Leadership and Digital Transformation have a significant effect on employee work effectiveness (F = 18.716; sig. = 0.000). The coefficient of determination (R²) value of 0.291 indicates that both variables are able to explain 29.1% of the variation in employee work effectiveness. This study concludes that employee work effectiveness is more influenced by the success of digital transformation implementation than individual digital leadership. Therefore, the Gunungsitoli City Government needs to strengthen digital transformation through infrastructure development, system integration, increasing digital competency of the apparatus, and strengthening digital leadership capacity on an ongoing basis.